Brain regions involved in prospective memory as determined by positron emission tomography - Burgess, Paul W.; Quayle, Angela; Frith, Christopher D. (Neuropsychologia, 2001)
Prospective memory (PM) refers to the functions that enables a person to carry out an intended act after a delay. Despite the ubiquity of this behaviour, little is known about the supporting brain structures and the roles that they play. In this study, eight healthy participants performed four different PM tasks, each under three conditions: a baseline, and two conditions involving an intention. In the first of the intention conditions, subjects were asked to make a novel response to a certain class of stimuli whilst performing an attention-demanding task. However, the expected stimuli never actually occurred. In the second intention condition subjects were expecting to see these stimuli as before, and they did occur on ≈20% of trials. Relative to the baseline condition, increases in regional cerebral blood flow (rCBF) as estimated by oxygen-15 positron emission tomography technique across all four tasks were seen in the frontal pole (Brodmann's area 10) bilaterally, right lateral prefrontal and inferior parietal regions plus the precuneus when subjects were expecting a PM stimulus regardless of whether it actually occurred. Further activation was seen in the thalamus when the PM stimuli occurred and was acted upon, with a corresponding rCBF decrease in right lateral prefrontal cortex. It is argued that the first set of region play a role in the maintenance of an intention, with the second set involved additionally in its realisation.